METTL3 Facilitates Oral Squamous Cell Carcinoma Tumorigenesis by Enhancing c-Myc Stability via YTHDF1-Mediated m6A Modification - Wei Zhao; Yameng Cui; Lina Liu; Xiaozhou Ma; Xiaoqian Qi; Yue Wang; Zihao Liu; Shiqing Ma; Jingwen Liu; Jie Wu (Elsevier, 2020)
N6-Methyladenosine (m6A) is the most common internal modification of eukaryotic messenger RNA (mRNA) that occurred on the N6 nitrogen of adenosine. However, the roles of m6A in oral squamous cell carcinoma (OSCC) are still elusive. Here, we investigate the function and mechanism of methyltransferase-like 3 (METTL3) in OSCC tumorigenesis. Clinically, METTL3 was significantly upregulated in tissue samples and correlated with the poor prognosis of OSCC patients. Functionally, loss and gain studies illustrated that METTL3 promoted the proliferation, invasion, and migration of OSCC cells in vitro, and METTL3 knockdown inhibited tumor growth in vivo. Mechanistically, methylated RNA immunoprecipitation sequencing (MeRIP-seq) illustrated that METTL3 targeted the 3' UTR (near to stop codon) of the c-Myc transcript to install the m6A modification, thereby enhancing its stability. Furthermore, results revealed that YTH N6-methyladenosine RNA binding protein 1 (YTH domain family, member 1 [YTHDF1]) mediated the m6A-increased stability of c-Myc mRNA catalyzed by METTL3. In conclusion, our findings herein identify that METTL3 accelerates the c-Myc stability via YTHDF1-mediated m6A modification, thereby giving rise to OSCC tumorigenesis.